Electro-acupuncture for long COVID neuropsychiatric symptoms: study protocol for a prospective, randomized sham-controlled, patient-assessor-blinded clinical trial - Wei, Dong-jue; Chow, Chun-wai; Cheung, William Y. H.; Yeung, Wing-fai; Cao, Pei-hua; Liong, Ching; Chen, Hai-yong; Zhang, Shipping; Zhong, Linda L. D. (Frontiers in Medicine, 2025)
IntroductionPatients recovering from long COVID often endure a spectrum of neuropsychiatric symptoms, including cognitive impairment, memory deficits, mood disturbances and sleep disorders, that significantly impact their quality of life. Acupuncture, particularly electroacupuncture, has shown promise in addressing these symptoms. Currently there is no high-quality clinical trial for acupuncture on long COVID neuropsychiatric symptoms.Methods and analysisIn this 24 weeks, sham-controlled, patient-assessor-blinded randomized trial, 150 long COVID patients will be equally allocated to either an electroacupuncture group (EAG) or a sham control group (SCG). Each subject will receive a total of 32 intervention sessions over a 16 weeks intervention phase (two sessions each week) and will be followed up for an additional 8 weeks. Primary outcomes include changes in the Mini-Mental State Examination (MMSE) and the Chinese version of the Beck Depression Inventory (CBDI) scores. Secondary outcomes include the Insomnia Severity Index (ISI), Brief Fatigue Inventory-Taiwan (BFI-T), and the Short Form 12 (SF-12). All outcomes will be assessed at baseline and then at 4 weeks intervals during both the treatment and post-treatment periods.DiscussionThis trial aims to generate robust clinical data on the therapeutic effects of electroacupuncture for long COVID. The anticipated results will clarify electroacupuncture’s value as a therapeutic option for neuropsychiatric symptoms in long COVID patients, contributing to evidence-based practice in integrative medicine.